2018
DOI: 10.1183/13993003.01587-2018
|View full text |Cite
|
Sign up to set email alerts
|

The added value of comorbidities in predicting survival in idiopathic pulmonary fibrosis: a multicentre observational study

Abstract: This is the first ever validated clinical prediction model and point score index for all-cause mortality in IPF to include comorbidity variables. Their inclusion significantly improved prediction of survival beyond demographic and physiological parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 35 publications
2
45
1
2
Order By: Relevance
“…When we adjusted the effects from the GAP stages for pulmonary co-morbidity, we noted that effect of the stage III group on mortality was reduced compared with stage I. This corroborates the recent trend to introduce comorbidity in prognostic indices [36]. Our cubic spline analyses of the continuous predictors age at diagnosis, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…When we adjusted the effects from the GAP stages for pulmonary co-morbidity, we noted that effect of the stage III group on mortality was reduced compared with stage I. This corroborates the recent trend to introduce comorbidity in prognostic indices [36]. Our cubic spline analyses of the continuous predictors age at diagnosis, Fig.…”
Section: Discussionsupporting
confidence: 82%
“…However, baseline FVC does only have limited prognostic value and longitudinal changes in FVC have some weaknesses [63]. Therefore, composite scoring systems incorporating lung physiology, sex and age are deemed more accurate at predicting mortality [64,65]. It is recognised that biomarkers may augment these models and improve prognostication in IPF.…”
Section: Prognostic Biomarkersmentioning
confidence: 99%
“…The German INSIGHTS IPF registry has determined that an increased number of comorbidities decreases HRQL [191]. Recently, the novel comorbidity assessment TORVAN model has shown that comorbidities may refer to a lower survival rate based on clinical and physiological parameters as in the GAP index [192]. While no effects of antifibrotic drugs on comorbidities have been reported so far, several reports focused on the effects of comedications or treatments of comorbidities in IPF.…”
Section: Treatment Of Comorbiditiesmentioning
confidence: 99%
“…Die Auswertungen von großen randomisierten Studien [11 -13] Ein früheres Krankheitsauftreten ist bei den familiären Formen der IPF möglich und mehrfach beschrieben [17,19]. Dennoch sollte man bei jüngerem Alter der betroffenen Patienten immer auch an die Möglichkeit einer pulmonalen Manifestation einer Autoimmunerkrankung denken [20].…”
Section: Epidemiologieunclassified